Innovative Strategy of Community Strengthening in Realizing Sustainable Tourism at Ciwidey's Dream Stop - Yati; Siswanto, Romi; Kadarisman; Jaya, Fitra; Sucipto (International Journal of Green Tourism Research and Applications, 2024)
This study aims to address this gap by exploring innovative strategies to enhance community capacity, thereby promoting sustainable tourism that benefits both the environment and the local economy. Sustainable tourism has gained prominence in both academic research and industry practice over the past decade, particularly in regions like Ciwidey, West Java, where natural beauty attracts a growing number of tourists. This increase in tourism brings both economic opportunities and significant environmental and social challenges, creating a need to balance economic growth with environmental preservation and community welfare. While existing literature emphasizes the importance of sustainable tourism, there is a noticeable gap in understanding how to build community capacity to manage these challenges effectively. Previous studies have often treated economic, social, and environmental aspects separately, lacking a comprehensive approach that integrates all three dimensions in a local context like Ciwidey. Given the strain on Ciwidey’s natural resources and the uneven distribution of tourism benefits, it is urgent to develop strategies that ensure equitable and sustainable economic development. By focusing on these issues, the research seeks to provide practical solutions that empower local communities to actively participate in and benefit from sustainable tourism. The study found that despite a growing awareness of sustainable tourism, significant barriers remain, such as limited resources and a lack of education and training. The success of sustainable tourism initiatives in Ciwidey depends largely on the community’s ability to engage effectively and take full advantage of the opportunities presented by inclusive tourism.